Odpowiedzi

2010-03-21T12:03:24+01:00
A) ( 1 + sinx ) ( 1/cosx - tgx ) = 1/cosx -tgx + sinx/cosx -sinxtgx =1/cosx -sinx/cosx +sinx/cosx -sinx*sinx/cosx =(1-sin2x)/cosx=cos2x/cosx=cosx
b) ( 1/sinx - 1/cosx ) ( sinx + cosx )=sinx/sinx+cosx/sinx-sinx/cosx-cosx/cosx=1+ctgx-tgx-1=ctgx-tgx
1 1 1
Najlepsza Odpowiedź!
2010-03-21T12:06:30+01:00
A) (1+sinx)(1/cosx-tgx)=cosx

L=(1+sinx)(1/cosx-tgx)=
(1+sinx)(1/cosx-sinx/cosx)=
(1+sinx)(1-sinx)/cosx=
(1-sin²x)/cosx=
cos²x/cosx=cosx=P

b)(1/sinx-1/cosx)(sinx+cosx)=ctgx-tgx

L=(1/sinx-1/cosx)(sinx+cosx)=
1+cosx/sinx-sinx/cosx-1=cosx/sinx-sinx/cosx=ctgx-tgx=P
8 3 8
2010-03-21T12:50:25+01:00
A)
( 1 + sinx ) ( 1/cosx - tgx ) = 1/cosx -tgx + sinx/cosx - sinxtgx = 1/cosx -sinx/cosx +sinx/cosx -sinx*sinx/cosx = (1-sin2x)/cosx= cos2x/cosx =cosx

Odp.Wynik to cosx .

b)
( 1/sinx - 1/cosx ) ( sinx + cosx ) =sinx/sinx+cosx/sinx-sinx/cosx-cosx/cosx =1+ctgx-tgx-1 =ctgx-tgx


Odp. Wynik to ctgx-tgx .
2 1 2